ІНТЕРАКТИВНЕ НАВЧАННЯ АНГЛІЙСЬКОГО ДІАЛОГІЧНОГО МОВЛЕННЯ УЧНІВ ПОЧАТКОВОЇ ШКОЛИ - Kochubey, N (Continuing Professional Education: Theory and Practice, 2019)
The interactive teaching stages of primary school pupils’ English dialogical speech are considered in the article. The interactive teaching stages of English dialogical speech were characterized, the selection criteria of interactive methods and teaching means for forming English dialogical speech abilities and skills according to the stages were examined, the interactive teaching system of primary school pupils’ English dialogical speech was suggested.